Designing a Robust and Versatile System to Investigate Nutrient Exchange in, and Partitioning by, Mycorrhiza (Populus x canesces x Paxillus involutus) Under Axenic or Greenhouse Conditions - Schreider, Katharina; Boy, Jens; Sauheitl, Leopold; Figueiredo, Aline Fernandes; Andrino, Alberto; Guggenberger, Georg (Frontiers in Fungal Biology, 2022)
Phosphorus (P) bioavailability affects plant nutrition. P can be present in soils in different chemical forms that are not available for direct plant uptake and have to be acquired by different mechanisms, representing different resource niches. These mechanisms, of which many seem to be attributed to mycorrhiza, likely influence the diversity and stability of plant communities in natural ecosystems, as they also might help to overcome a future shortage of P supply in agro-ecosystems. In order to understand the mechanisms of P acquisition, the associated carbon costs, and the resource partitioning by mycorrhizal fungi, the ecosystem situation has to be mimicked in smaller scaled experiments. Here, different experimental setups are evaluated using plantlets of Populus x canescens and its functional ectomycorrhizal (ECM) fungus Paxillus involututs strain MAJ. To investigate resource partitioning involving mycorrhizae, the protocols of this study describe preparation of an in vitro and a rhizotrone culture systems for studies under axenic conditions as well as a mesocosm culture system for greenhouse conditions. We also describe the construction of separate compartments containing nutrients and excluding plant roots as well as the progress that has been made in in vitro propagation of plant and ECM fungal material. The practical experience made in our study shows that the in vitro culture system is prone to desiccation and its construction and maintenance are more time consuming and complicated. In contrast, with the axenic rhizotrone culture system and the mesocosms we have created more robust and very versatile systems that are also suitable for greenhouse conditions.